2022
DOI: 10.1155/2022/5574242
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Design of a Solar Rotary Dryer Bench Test for Phosphate Sludge

Abstract: As an eco-friendlier way to manage mining waste, the use of solar energy to dry phosphate sludge in a rotary dryer is envisioned. As a first step toward this end, a design study for a bench-scale rotary dryer for phosphate sludge is detailed, using a one-dimensional mathematical model developed for this task. Using the Engineering Equation Solver (EES) software, a steady-state transport phenomena model was developed that enables an estimation of the moisture and temperature profiles for both gas and product in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…This apparatus, consisting of a continuously rotating cylinder or drum, receives heat from an energy source such as biomass and is particularly appropriate for granular food products like grains [6]. The widespread adoption of rotary dryers across various applications, including heating, cooling, mixing, and drying processes, can be attributed to their ability to provide uniform drying, ease of operation, and costeffectiveness [7][8][9]. The design of these dryers is tailored to utilize waste energy sources that are readily available and economically viable, making them well-suited for rural farming communities.…”
Section: Figure 1 Black Soldier Fly Life Cycle [1]mentioning
confidence: 99%
“…This apparatus, consisting of a continuously rotating cylinder or drum, receives heat from an energy source such as biomass and is particularly appropriate for granular food products like grains [6]. The widespread adoption of rotary dryers across various applications, including heating, cooling, mixing, and drying processes, can be attributed to their ability to provide uniform drying, ease of operation, and costeffectiveness [7][8][9]. The design of these dryers is tailored to utilize waste energy sources that are readily available and economically viable, making them well-suited for rural farming communities.…”
Section: Figure 1 Black Soldier Fly Life Cycle [1]mentioning
confidence: 99%
“…Sun drying is very dependent on the weather and causes fatigue to workers due to sun exposure. The dryer design in Figure 1 has been tested to dry corn, fruit lunkhead, and red chili [25,26,27]. From several tests carried out, it was found that there was a significant increase in temperature and a shorter drying time than sun drying.…”
Section: Figurementioning
confidence: 99%
“…Rotary dryers in the form of cylinders or drums that rotate continuously with energy from biomass are very suitable for use by small farmers. Mixing, cooling, heating, and drying processes for granular materials widely use rotary drums [10,11,12]. Rotary dryers with rice husk energy sources are carried out using the energy conversion method using a heat exchanger.…”
Section: Introductionmentioning
confidence: 99%